Purpose and effectiveness of psychoeducation in patients with bipolar disorder in a bipolar clinic setting. (15th April 2013) - Stafford, N.; Colom, F.
Abstract : Objective: This article reviews psychological therapies in the treatment of bipolar disorder, in particular psychoeducation, and how the inclusion of four fundamental principles – patient/therapist communication, flow of information, patient involvement and a trusting relationship – can improve patient outcomes. Method: The content of this article is based on the proceedings of a 1‐day standalone symposium in November 2011 exploring how to establish a bipolar clinic within the context of existing services in the UK's National Health Service. Results: Certain psychological interventions have emerged as beneficial add‐on treatments to pharmacotherapy in bipolar disorder and are associated with greater stabilisation of symptoms, fewer relapses and longer time to relapse. Psychoeducation is a simple approach to support prevention of future episodes by delivering behavioural training to improve illness insight, early symptom identification and development of coping strategies. Empowering patients to actively participate in their treatment provides independence, counteracts the current disconnect of therapist and patient, and increases awareness and understanding of the challenges of living with and treating bipolar disorder. Conclusion: Psychoeducation enables patients to understand bipolar disorder, get actively involved in therapy planning, and be aware of methods for episode prevention, therefore effectively contributing to improved treatment outcomes and patient quality of life.